Verbal retrieval cues prevent renewal and spontaneous recovery of predictive judgments in university students - Alvarado García, Angélica Serena (2018)
Long-term effectiveness is one of the major problems of psychotherapy because successfully eliminated unhealthy behaviors may reappear relatively easily under certain contextual changes. In two experiments, we explored the impact of verbal retrieval cues on renewal and spontaneous recovery in humans. During the first phase, all participants learned a relationship between one cue and one outcome (X-O1). The following phase involved a change in the original relationship (X-O2). Finally, participants were presented with cue X and asked about the relationships with both outcomes. Half of the participants were asked to remember Phase 2, while the other half did not receive any instruction at all. In Experiment 1, testing took place in a different context, while participants in Experiment 2 were tested after two days. The results indicated that remembering Phase 2 eliminated both renewal and spontaneous recovery. Our findings are discussed under the contemporary learnin theory. We also mention the probable benefits in therapeutic settings.